Application of the repetitions in reserve-based rating of perceived exertion scale for resistance training - Helms, E. R.; Cronin, J.; Storey, A.; Zourdos, M. C. (Strength and Conditioning Journal, 2016)
Ratings of perceived exertion are a valid method of estimating the intensity of a resistance training exercise or session. Scores are given after completion of an exercise or training session for the purposes of athlete monitoring. However, a newly developed scale based on how many repetitions are remaining at the completion of a set may be a more precise tool. This approach adjusts loads automatically to match athlete capabilities on a set-to-set basis and may more accurately gauge intensity at near-limit loads. This article outlines how to incorporate this novel scale into a training plan.